H(5)dotasa (=(alpha RS)-alpha-(carboxymethyl)-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), an asymmetrical derivative of H(4)dota (=1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) substituted at one acetate pendant arm: H-1-NMR and potentiometric studies of the ligand and its lanthanide(III) complexes - André, João P. (2005)
The ligand H5dotasa (=(alphaRS)-alpha-(carboxymethyl)-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) is a H4dota-like macrocyclic ligand with a carboxymethyl CH2COOH substituent moiety at the C(alpha) atom of one of the four acetate pendant arms of H4dota (=1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), present as a racemic mixture of (alphaR) and (alphaS) enantiomers. The protonation constants of the ligand were determined by potentiometry, giving values close to H4dota except for the extra pK3 value of 5.35 assigned to protonation of the extra carboxylate group in the alpha-substituted (=succinic acid) pendant arm. The 1H-NMR spectra of H5dotasa at different pH values are too complex to allow the determination of its microscopic protonation scheme, due to the presence of multiple isomeric structures in solution. The thermodynamic stability constant of its Gd3+ chelate was determined by a potentiometric method, and the value obtained, log KML = 27.2 (0.2), is higher than for the [Gd(dota)(OH2)]- complex. The solution structure of the asymmetrical Ln3+ chelates of dotasa was studied by 1H-NMR spectroscopy, indicating the presence of four isomers, corresponding to the combination of the antiprismatic (M) and twisted antiprismatic (m) helicities of the pendant arms and to the (alphaR) and (alphaS) configurations of the substituted pendant arm. The m/M isomer ratio decreases along the lanthanide series, with the m isomer decreasing from 90% at La to about 50% from Eu-Lu. This shows that the expected m isomer population of the [Gd(dotasa)(OH2)]2- complex is higher than for the unsubstituted [Gd(dota)(OH2)]- (circa 15%) but lower than for a Gd3+ chelate of a alpha-alpha’-alpha’’,alpha’’’-tetrasubstituted(RRRR)-configurated dota (circa 70%). Thus the stabilisation of the m isomer by C monosubstitution at the dota acetate pendant arms in [Gd(dotasa)(OH2)]2- is responsible for its increased H2O exchange rate and higher relaxivity.